Differences in Spatial Physical Activity Patterns between Weekdays and Weekends in Primary School Children: A Cross-Sectional Study Using Accelerometry and Global Positioning System - Rahel Bürgi; Eling D. de Bruin (MDPI AG, 2016)
Targeting the weekend to promote physical activity (PA) in children seems to be promising given that they tend to be less physically active and, particularly, as the age-related decline in PA is more marked during weekends. Considering the ambiguity of why children are not able to maintain their PA level on weekends, the aim of the present study was to objectively investigate differences in children's spatial PA patterns between week and weekend days using the combination of Global Positioning System (GPS) and accelerometry. Seventy-four second graders (aged 7-9 years) and 98 sixth graders (aged 11-14 years) wore an accelerometer and GPS sensor for seven consecutive days to determine where children spend time and engage in PA. Time-matched accelerometer and GPS data was mapped with a geographic information system and multilevel analyses accounting for the hierarchical structure of the data were conducted. Differences between weekdays and weekends regarding the total time spent and the absolute and relative level of PA in various settings were found in both age groups. The findings support previous research pointing to the importance of targeting weekend PA, especially when children grow older. Future interventions should encourage children to use outdoor spaces more frequently on weekends, rather than stay at home, and to commute actively to destinations other than school.